An Unusual Cause of Chronic Scrotal Pain Coexisting with Hydrocele: Isolated Tuberculous Epididymitis - İbrahim Kartal; Fatih Sandıkçı; Ünsal Han; Azmi Levent Sağnak; Hamit Ersoy (Journal of Urological Surgery, 2019)

(untitled)
Isolated tuberculous epididymitis (ITE) is a rare condition affecting only the epididymis without clinical evidence of renal involvement. One of the causes of chronic scrotal pain can be ITE, which is usually only diagnosed in the presence of strong clinical suspicion, as it was in this case. The patient who had chronic scrotal pain and hydrocele and who did not respond to medical treatment for the diagnosis of epididymitis underwent scrotal exploration. The pathology material demonstrated necrotizing and non-necrotizing granulomas in the epididymis and around the small vessels. The Mantoux test performed for differential diagnosis produced a positive result. The polymerase chain reaction done on the pathology material also produced results compatible with mycobacterium tuberculosis. The patient, who did not have postoperative systemic complaints, had his scrotal pain and swelling resolved with the completion of a 6-month anti-tuberculosis medical treatment. In ITE, which is rarely encountered, patients usually present with a painless scrotal mass. It must be taken into account that ITE may unusually cause scrotal pain, and even though not emphasized thoroughly until now, it may be accompanied by hydrocele as in our patient.